Coaching culture in the context of the emergence of creative class - Kotylak Sławomir; Michałowska Mariola; Danielak Wiesław (Management, 2015)
The aim of the paper is to present on the basis of the study of literature the essence of coaching, the creative industries in the modern economy, the culture of coaching in relation to the creative class as well as issues relating to the development of relations between the client and the coach.